2005
DOI: 10.1098/rspb.2005.3117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental quality and evolutionary potential: lessons from wild populations

Abstract: An essential requirement to determine a population's potential for evolutionary change is to quantify the amount of genetic variability expressed for traits under selection. Early investigations in laboratory conditions showed that the magnitude of the genetic and environmental components of phenotypic variation can change with environmental conditions. However, there is no consensus as to how the expression of genetic variation is sensitive to different environmental conditions. Recently, the study of quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
502
10
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(558 citation statements)
references
References 100 publications
(132 reference statements)
42
502
10
4
Order By: Relevance
“…(b) Behavioural and evolutionary niche expansion Many studies show that genetic variation has a greater impact on population parameters under strong selection (reviewed in Wise et al 2002;Armbruster & Reed 2005;Charmantier & Garant 2005). Our results contribute to this literature by showing that the impact of genetic variation also depends on the degree of intraspecific resource competition.…”
Section: Discussionsupporting
confidence: 73%
“…(b) Behavioural and evolutionary niche expansion Many studies show that genetic variation has a greater impact on population parameters under strong selection (reviewed in Wise et al 2002;Armbruster & Reed 2005;Charmantier & Garant 2005). Our results contribute to this literature by showing that the impact of genetic variation also depends on the degree of intraspecific resource competition.…”
Section: Discussionsupporting
confidence: 73%
“…The most consistent explanation for this pattern is that genetic variation has not been effectively eroded by natural selection in the novel environment [4,17]. This may also apply to our observations, but it is difficult to relate these explanations to domestic animals with a short history in captivity.…”
Section: Changes In Heritabilitysupporting
confidence: 57%
“…Several studies have shown elevated genetic variation for continuously varying traits, such as body size, in stressful or novel environmental conditions, though opposite observations exist especially for wild populations (reviewed by [4,15,16]). The most consistent explanation for this pattern is that genetic variation has not been effectively eroded by natural selection in the novel environment [4,17].…”
Section: Changes In Heritabilitymentioning
confidence: 99%
“…In contrast to pathogen-induced changes, changes in heritabilities due to other biotic (e.g. diet) and abiotic factors have been a focus of active research (Kause & Morin, 2001 ;Charmantier & Garant, 2005). The focus here was on the analysis of field data, but the statistical method presented is applicable to experimental treatments as well.…”
Section: (I) Random Regression Modelsmentioning
confidence: 99%